Bitcoins within Georgia s Money Laundering Scheme - Mikeladze, Aleksandre (European Journal of Economics and Business Studies, 2017)
Bitcoins technology brings a new level of innovation to business and communication across the world. However, the advantages of a virtual currency payment system face the threat from criminal activities occurring over a pseudonymous network where there is virtually no current regulation to cover illegal transactions. The current situation in Georgia is as follows: the second Bitcoin s processing datacenter has opened in Georgia. While the virtual money is new even in developed countries, more unusual it is for Georgia, where local economists are more skeptical toward cryptocurrency. Therefore, they believe that electronic money is not controlled by any central bank that gives a lot of opportunities for illegal transactions. According to the Georgian experts, bitcoin is a very risky currency that can be used for money laundering, as it is completely uncontrolled. However, the Georgian central bank system claims that bitcoins are not dangerous, and the lack of awareness gives rise to talk about money laundering. The biggest challenge seems to be regulation of Bitcoin without hindering the potential for growth. While there is usually certainly a chance that Bitcoin could fail or be pushed out of existence by a more innovative technology, policymakers must be careful not to hinder a technology that could change the way global economy functions.